Perencanaan Pengembangan Sarana Pendidikan melalui Rencana Kerja dan Anggaran Sekolah (RKAS): Studi Kasus di SMAN 2 Koto Baru - Alfadila Hasan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the planning process for the development of educational facilities at SMAN 2 Koto Baru, identify the supporting and inhibiting factors, and examine the strategies implemented by the school to enhance the quality of its educational facilities. A qualitative research approach with a descriptive design was employed. Data were collected through observations, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the planning of educational facilities at SMAN 2 Koto Baru is conducted systematically through a series of stages, including needs identification, assessment of existing facilities, priority setting, and the preparation of the School Work Plan and Budget (RKAS). This process involves the principal, vice principal for facilities and infrastructure, teachers, administrative staff, and the school committee. The supporting factors include government financial assistance through the School Operational Assistance (BOS) Fund, active participation from the school community, and the principal's strong leadership commitment. Meanwhile, the main challenges comprise limited financial resources, the increasing demand for technology-based learning facilities, and space constraints. The study recommends diversifying funding sources and conducting regular evaluations to ensure sustainable educational facilities planning that effectively supports continuous improvements in teaching and learning quality.